Besides of large ocean and long coastline, Indonesia was also gifted resourceful islands, which were economically potential for our state development. Even the outer small islands were also have a strategic point as a base line from the Indonesian archipelago straight line in reconciling Indonesian water area, as the front liners of the state, and also support international passage. Nipa is one of the outer small islands that were recently being a public issue. Most of it was the anxiousness abo - Endang Adiyanto; Etty Eidman; Luky Adrianto (Buletin Ekonomi Perikanan, 2007)
Besides of large ocean and long coastline, Indonesia was also gifted resourceful islands, which were economically potential for our state development. Even the outer small islands were also have a strategic point as a base line from the Indonesian archipelago straight line in reconciling Indonesian water area, as the front liners of the state, and also support international passage. Nipa is one of the outer small islands that were recently being a public issue. Most of it was the anxiousness about the sinking of Nipa and coast reclamation by Singapore. Both of them concerned to be the causes of a significantly water area diminishing as the base line measurement changes between bordered states. That anxiousness was reasonable as concerning the lost of SipadanLigitan of which Indonesia and Malaysia disagreement. We need some juridical revision for the principal of outer small islands. Afterward, some management policy aspect is complementary required. This research was using a case study method compiled with formally juridical method. Primary and secondary data were analyzed with a qualitative analysis. This issue has three juridical law anvil of Indonesian ownership for Nipa Island, the Intemational Law, Bilateral Agreements, and National Law. From a juridical study, it is notorious that stronger law anvils compared with Sipadan and Ligitan supported Nipa and the other islands. Otherwise, the policy aspect contents about the issues and management strategies conducted by the government, which is mandatory, associated by MMAF, Ministry of Foreign Affairs and Ministry of Defends. The matrix policy described that the MMAF mostly participated than the others. Although it has strong law anvils for Nipa issues, Indonesia is forced to be concern about patches, which can be utilized by Singapore, as example for accomplishments of the baseline agreement and their activity construct in that island.